Statistical Methods for Food Science : Introductory Procedures for the Food Practitioner - Bower, John A. (Lecturer in food science) (Chichester, West Sussex, UK : Wiley Blackwell, 2013)
The recording and analysis of food data are becoming increasingly sophisticated. Consequently, the food scientist in industry or at study faces the task of using and understanding statistical methods. Statistics is often viewed as a difficult subject and is often avoided because of its complexity and a lack of specific application to the requirements of food science. This situation is changing - there is now much material on multivariate applications for the more advanced reader, but a case exists for a univariate approach aimed at the non-statistician. This book provides a sourc.
5.4.1 Related pairs and groups5.4.2 Ordinal scales; 5.4.3 Independent groups; 5.4.4 Other non-parametric tests; 5.5 Significance tests for interval and ratio data (parametric); 5.5.1 t-tests; 5.5.2 Analysis of variance (ANOVA); References; Chapter 6 Association, correlation and regression; 6.1 Introduction; 6.2 Association; 6.3 Correlation; 6.3.1 Main features of correlation; 6.3.2 Correlation analysis; 6.3.3 Correlation application; 6.4 Regression; 6.4.1 Main features of regression; 6.4.2 Regression analysis; 6.4.3 Regression assumptions; 6.4.4 Regression application; References.
Includes bibliographical references and index.
Print version record.
Keywords: Food -- Research -- Statistical methods; Nutrition -- Statistical methods; TECHNOLOGY & ENGINEERING -- Food Science; Food -- Research -- Statistical methods; Nutrition -- Statistical methods; Electronic books; Electronic books